Дослідження відновлення деталей шестеренних насосів пластичним деформуванням - Іванкова, О. В.; Федін, В. О.; Ivankova, O.; Fedin, V. (ЦНТУ, 2025)
Відновлення зношених деталей сільськогосподарської техніки дає змогу суттєво скоротити час простою машин, а також підвищити якість ремонту та позитивно впливати на показники довговічності машин. На зараз існує потреба в дослідженнях використання технологій, що ґрунтуються на пластичній деформації у ремонті конкретних деталей. Актуальним наразі є аналіз можливості застосування пластичного деформування у відновленні зношених втулок шестеренних насосів гідросистем автотракторної техніки. Для цього дослідили залежність зміни об’єму втулки від зміни її геометричних параметрів при відновленні пластичним деформуванням (осадженням) тощо. Restoration of worn parts of agricultural machinery allows to significantly reduce the downtime of machines, as well as to improve the quality of repairs and positively affect the durability of machines. Currently, there is a need for research into the use of technologies based on plastic deformation in the repair of specific parts. Gear pumps are an important component of hydraulic systems of machines. Not only the efficiency of the unit, but also the quality of control and adjustments depends on the operation of the pumps. Currently, the analysis of the possibility of using plastic deformation in the restoration of worn bushings of gear pumps of hydraulic systems of autotractor equipment is relevant. To this end, the dependence of the change in the volume of the bushing on the change in its geometric parameters during restoration by plastic deformation (deposition) was investigated. Currently, the analysis of the possibility of using plastic deformation in the restoration of worn bushings of gear pumps of hydraulic systems of autotractor equipment is relevant etc.
Research on the Restoration of Gear Pump Parts by Plastic Deformation
Keywords: насос; відновлення; довговічність; зношування; pump; restoration; durability; wear